Abdominal admittance helps to predict the amount of fluid accumulation in patients with acute heart failure syndromes. Issue 4 (April 2016) - Taniguchi, Tatsunori; Hamano, Go; Koide, Masao; Hirooka, Keiji; Koretsune, Yukihiro; Kusuoka, Hideo; Ohtani, Tomohito; Sakata, Yasushi; Yasumura, Yoshio
Abstract: Background: Predicting fluid volume that needs to be removed in acute heart failure syndromes (AHFS) patients remains challenging. Thoracic admittance (TA), the reciprocal of thoracic impedance measured by bioelectrical impedance, reflects the amount of fluid in the thorax. Abdominal organs play an important role in AHFS as systemic fluid reservoirs. We investigated the relationship between abdominal admittance (AA) at the time of admission for AHFS and net fluid loss (NFL) during hospitalization. Methods: Sixty-two consecutive patients hospitalized for AHFS [age 71 ± 10 years, left ventricular ejection fraction (LVEF) 39 ± 17%] were studied. The admittance values, i.e. the reciprocals of the impedance values, were derived using a BioZ ® (CardioDynamics, San Diego, CA, USA). The change in weight from admission to discharge was used as a surrogate of amount of NFL. Results: At the time of admission, a significant correlation was detected between TA and AA ( r  = 0.46, p  = 0.0001). TA at admission was significantly correlated with the LV structural variables (end-diastolic dimension and end-systolic dimension), and serum sodium level. AA at admission was significantly correlated with New York Heart Association (NYHA) class and plasma BNP, and also correlated with LVEF and variables related to systemic congestion [minimal inferior vena cava (IVC) diameter and tricuspid regurgitation grade]. Neither TA nor AA values were significantly correlated with weight at admission. During hospitalization, TA and AA declined from 44 ± 8 kΩ −1 to 36 ± 6 kΩ −1 ( p  < 0.0001) and from 74 ± 25 kΩ −1 to 56 ± 17 kΩ −1 ( p  < 0.0001), respectively. Weight fell from 60.1 ± 10.8 kg to 54.5 ± 9.4 kg ( p  < 0.0001), while NFL was 5.8 kg (range, 0.1–17.5 kg). In univariate analyses, the admission NYHA class, TA, AA, weight, and IVC diameter correlated with NFL. Multivariate analysis demonstrated that only admission weight [standardized partial regression coefficient (SPRC) = 0.596], AA (SPRC = 0.529), and NYHA class (SPRC = 0.277) were independent predictors of NFL. Conclusion: Abdominal admittance measurement helps to predict the amount of fluid volume to be removed in patients with AHFS.